How WWF partnered with Nokia to promote conservation - Minton, Graham (Henry Stewart Talks, 2017)
The case study examines one example of the partnerships that WWF forms with leading companies to improve environmental outcomes. In this example, published in 2009, Nokia asked WWF to engage staff and advise them on business practices, in order improve their environmental performance over time.